Parricídio: maus tratos sofridos na infância - Teche, Ana Maria Freitas (2014)
Parricide is the parents murder by their children. It involves the act of patricide and matricide. Patricide is the crime committed by the child against the father and matricide is against the mother. The purpose of this study was to identify parenting education practices and maltreatment (physical, psychological and sexual) endured by parricides who were serving time in prisons and Civil Police Stations of the state of Paraná. Three parricides participated in the research, two patricides and one matricide, all male, ages 27, 39 and 42 in different locations. Four tools were used to gather data: a structured interview, PSI - Parenting Style Inventory (Gomide, 2006), a questionnaire on Sexual Abuse Prevalence and a data-sheet to capture data through processes. Data gathered through the interviews, the questionnaire on sexual abuse prevalence and the processes was presented as case study and data obtained through PSI was discussed and reviewed individually based on literature. Then the data was correlated with each participant. Parenting style indexes achieved risk scores and it was found that every parricide went through childhood marked by physical and emotional maltreatment and negligence, and two of them were sexually abused. This study emphasizes the need of studying intervention and treatment options intended for reintegrating the parricide to society.